Analysis of The Influence of Digital Infrastructure on Students' Learning Outcomes at Al-Birru Elementary School, Sukabumi District - Abdul Aziz, Muh; Rinawati, Rinawati; Madhakomala, R. (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to analyze the effect of digital infrastructure on student learning outcomes at SD Albirru, Sukabumi Regency. Adequate digital infrastructure is believed to increase the effectiveness of learning, which leads to improved student academic outcomes. This study uses a quantitative approach with a descriptive correlational research design. The research sample consisted of teachers and parents of students involved in digital learning at SD Albirru, with a total of 50 respondents selected using a census sampling technique where the entire population was sampled. Data were collected through closed questionnaires that had been tested for validity and reliability, then analyzed using multiple regression with the help of SPSS 26. The results of the study indicate that digital infrastructure has a significant positive effect on student learning outcomes, where improving the quality of digital infrastructure (such as stable internet access, adequate hardware, and digital learning platforms) contributes to improving student academic outcomes. This finding is in line with previous studies that emphasize the importance of digital infrastructure in supporting more effective learning. Based on the results of the study, it is recommended to improve the quality of digital infrastructure in schools to create a more interactive and enjoyable learning environment. This study also contributes to the development of technology-based education policies at the elementary school level.